3, 4, 5‐O‐tricaffeoylquinic acid alleviates ionizing radiation‐induced injury in vitro and in vivo through regulating ROS/JNK/p38 signaling. Issue 2 (6th November 2021) - Liu, Jiajun; Hu, Wen; Ma, Xiaoying; Liang, Xin; Lin, Long; Huang, Jianming; Liu, Jianwen
Abstract: Ionizing radiation (IR) brings many health problems to humans, causing damage to the digestive system, hematopoietic system, and immune system. Natural compounds derived from plants have attracted widespread attention due to their low toxicity. Here, we found that 3, 4, 5‐ O ‐tricaffeoylquinic acid (tCQA) extracted from natural plant Azolla imbricata could significantly alleviate the systemic damage in mice caused by IR. In order to further explore the molecular mechanism of the radioprotective effect of tCQA, in vitro experiments confirmed that tCQA could attenuate the cytotoxic effect of IR on the colonic epithelial cell line NCM460 and alleviate the IR‐induced mitochondrial dysfunction characterized by the decrease of mitochondrial transmembrane potential, ROS production, and caspase‐dependent apoptosis. In addition, the generation of ROS induced by H2 O2 could also be reversed by tCQA. Then, Western blot demonstrated that tCQA could reverse the MAPK signaling pathway activated by IR. However, the inhibitory effect of tCQA on JNK and P38 levels activated by the JNK agonist anisomycin is not obvious; meanwhile, tCQA could inhibit the activation of JNK/P38 induced by H2 O2, which suggests that tCQA might inhibit the JNK/P38 signaling pathway by reducing ROS. In short, tCQA inhibits the generation of ROS caused by IR, and then regulates the activity of caspase in the mitochondrial pathway by inhibiting the JNK/P38 signaling pathway, thereby alleviating the apoptosis of NCM460. This research provides an experimental basis for the development of new types of radioprotective agents for medical diagnosis and radiotherapy.